2003
DOI: 10.1038/nn1169
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-specific contribution of the superior colliculus to overt and covert shifts of attention

Abstract: The analysis of a peripheral visual location can be improved in two ways: either by orienting one's gaze (usually by making a foveating saccade) or by 'covertly' shifting one's attention to the peripheral location without making an eye movement. The premotor theory of attention holds that saccades and spatial shifts of attention share a common functional module with a distinct neuronal basis. Using single-unit recording from the brains of trained rhesus monkeys, we investigated whether the superior colliculus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
266
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(304 citation statements)
references
References 33 publications
30
266
1
1
Order By: Relevance
“…By contrast, responses of neurons with purely movementrelated activity were suppressed, suggesting that some neurons participate selectively in saccade production and others participate in covert visual selection. Similarly, another study that recorded neuronal activity in the SC while monkeys performed a visual discrimination task found that visuomovement neurons were active during covert shifts of attention (31). Thus, both the FEF and SC contain neurons that signal the locus of attention.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…By contrast, responses of neurons with purely movementrelated activity were suppressed, suggesting that some neurons participate selectively in saccade production and others participate in covert visual selection. Similarly, another study that recorded neuronal activity in the SC while monkeys performed a visual discrimination task found that visuomovement neurons were active during covert shifts of attention (31). Thus, both the FEF and SC contain neurons that signal the locus of attention.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, unless our observations were due primarily to antidromic activation of neurons outside the FEF, e.g., in the lateral intraparietal area (LIP), our results imply that FEF neurons, perhaps by way of other structures activated orthodromically, enhance representations in visual cortex during spatial attention. Indeed, the FEF projects to the superior colliculus (SC) and area LIP, two areas known to be involved in both saccade control and visual attention (23,27,28,31,32). Thus, there are several pathways by which FEF stimulation could act on visual responses.…”
Section: Discussionmentioning
confidence: 99%
“…Such selection-related activity occurs at the same time that neuronal activity in visual areas of the cortex is enhanced during attentional tasks (Reynolds and Desimone, 1999;Ghose and Maunsell, 2002). This SC selection-related activity is modulated when the monkey attends to a region of the visual field (Kustov and Robinson, 1996), and this modulation occurs only with a spatial cue for that region (Ignashchenkova et al, 2004). The logic then is that the delay activity of these SC neurons might be directed not only to preparing for a saccade to one part of the visual field but also to providing a spatial attention signal to cortex that modulates the activity of visual cortical neurons related to the same part of the visual field.…”
Section: Sc and Visual Spatial Attentionmentioning
confidence: 97%
“…1B) and project directly to the brainstem saccade generator (23)(24)(25). Functionally, these neurons have multisensory and oculomotor responses and have been shown to play a central role in spatial attention (19,20). This has led to the hypothesis that SCi is best described as a priority map for the control of attention and gaze (4) (Fig.…”
Section: Surround Modulation Emerges Earlier and Stronger In Scs Thanmentioning
confidence: 99%
“…1B) is multilayered but is often described as having two dominant functional layers, a superior colliculus superficial layer (SCs) associated exclusively with visual processing and a superior colliculus multisensory-cognitive-motor intermediate layer (SCi) linked to the control of attention and gaze (19)(20)(21)(22). Because SCs is interconnected with multiple visual areas (23-25), it is in an ideal location to pool diverse visual inputs to form a feature-agnostic saliency representation.…”
mentioning
confidence: 99%